A Moderated Mediation Model of Emotion Regulation and Work-to-Family Interaction: Examining the Role of Emotional Labor for University Teachers in Pakistan. (May 2022) - Saleem, Zohra; Hanif, Ayaz Muhammad; Shenbei, Zhou
This study develops an Employee Emotional Engagement Model in the work and family domain using structural equation modeling. The effects of transiting from work to family role are measured via the experience sampling method over 2 weeks from 126 university teachers. Multilevel modeling results indicate that family engagement worsened when employees engaged in surface acting but improved when they engaged in deep acting. Furthermore, work-to-family conflict mediates the negative relationship between surface acting and family engagement, while work-to-family enrichment mediates the positive relationship of deep acting on family engagement. Employees older in age, married, and with bigger family size predict a higher level of work-to-family conflict and lower level of work-to-family enrichment. Findings reveal that females experienced stronger enrichment from work to family while deep acting compared to males. Analyses also revealed that family engagement strongly predicts work engagement in employees.